Neobaroque in the Americas : Alternative Modernities in Literature, Visual Art, and Film - Kaup, Monika (Book collections on Project MUSE., 2012)
In a comparative and interdisciplinary analysis of modern and postmodern literature, film, art, and visual culture, the author examines the twentieth century's recovery of the baroque within a hemispheric framework embracing North America, Latin America, and U.S. Latino/a culture. As "neobaroque" comes to the forefront of New World studies, attention to transcultural dynamics is overturning the traditional scholarship that confined the baroque to a specific period, class, and ideology in the seventeenth century. Reflecting on the rich, nonlinear genealogy of baroque expression, this book envisions the baroque as an anti-proprietary expression that brings together seemingly disparate writers and artists and contributes to the new studies in global modernity